Devotion II - Pascual, Wilfredo (Archīum Ateneo, 2024)
In 2004, the author flew to New York to spend a few days with fans of Nora Aunor during the Philippine Superstar’s U.S. concert tour. This personal essay is a ruminative account of a wayfaring trip that began the year before, when the author flew to Manila and met the star for the first time. It’s a pilgrimage of sorts, tracking the wandering icon in Manhattan, from her hotel bedroom to Times Square all the way to the airport. It crosses time and space from aquatic Bicol and Atlantic City to the mystical Byzantine age and the tumultuous years of the Marcos dictatorship. It grapples with symbols and stories, the faith and powers at work in the act of devotion, at home or elsewhere.